Information Asymmetry and Accounting Disclosures for Joint Ventures - LIM, Chee Yeow (Institutional Knowledge at Singapore Management University, 2003)
In September 1999, the Financial Accounting Foundation issued a special report recommending the use of the equity method supplemented with appropriate disclosures for corporate joint ventures in the United States. This study, using data for corporate joint ventures in Singapore, provides some preliminary evidence regarding the effect of the supplementary information disclosure on information asymmetry among market participants as measured by bid-ask spreads. The results show that the disclosure of supplementary information of joint ventures is associated with a significant decline in bid-ask spreads. The results also indicate that the decline in information asymmetry is larger when the investment in joint ventures is significant and that larger investing firms tend to have a smaller decline in information asymmetry compared to smaller investing firms. The implications of this study, that the provision of supplementary information about joint ventures could reduce information asymmetry among participants in equity markets, thus leveling the playing field among traders, could have implications for policymakers.